Do no harm? Risk perceptions in national bioenergy policies and actual mitigation performance. (September 2017) - Goetz, Ariane; German, Laura; Hunsberger, Carol; Schmidt, Oscar
Abstract: This paper investigates how risks are anticipated in national bioenergy policies and in which way related expectations that harms can be prevented or mitigated have actually been met. The paper draws on the national biofuel policies of ten countries and the EU, selected to represent a diverse sample of regions, producers and consumers, and pioneers and latecomers. It proceeds in two steps: firstly, it identifies three risk categories most frequently mentioned across the investigated national policies. Secondly, it conducts a systematic review of available empirical research about biofuels' effects in these risk categories. Findings are discussed regarding the empirical conditions under which related expectations to do no harm have materialized or failed; and concerning the challenges of risks perception and management in actual policies. We observe issues of crop selection and inadequate sectoral governance of biofuels, but also challenges of large-scale modes of intensive production. Effective risk mitigation was often the result of risk adverse choices by contract farmers engaged in biofuels production. National policy documents have insufficiently conceptualized 'do no harm' concepts and strategies in place to address these performance issues; while remaining silent on the particular risk governance and accountability framework that keeps track of actual developments, commitments and responsibilities. Highlights: Describes predominant "do no harm" expectations of selected national biofuels policies. Analyzes "do no harm" performance regarding food security, land conflict, and biodiversity. Identifies methodological, experiential, and institutional problems of risk mitigation. Promotes realistic valuation of risk of biofuels production beyond singularity and technical "fixes".